EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN DISCOVERY LEARNING DITINJAU DARI KETERAMPILAN BERPIKIR KRITIS SISWA KELAS 5 SD - Riani Ayu Utami; Sri Giarti (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2020)
This study aims to determine the effectiveness of the application of Problem Based Learning and Discovery Learning models in the thematic learning of 5th grade students in primary schools in terms of critical thinking skills. The sample in this study was elementary school in the ylang and elementary school in the orchid group in Semarang Regency. The research sample was taken using probality technique, namely the sampling area or cluster sampling so that the research sample consisted of 6 elementary schools with a total of 110 students. The results of the study gained from the experimental class with a total student (N) of 56 students with an average value of 81.74, while the control class obtained an average value of 77.59 with (N) as many as 54 students. T test results obtained the value of the calculated t coefficient of 2.305 and a sig value of 0.023 <0.050, then Ho is rejected and Ha is accepted meaning that there are significant differences in the application of problem based learning and discovery learning models in terms of critical thinking skills of 5th grade students in elementary school on learning thematic.Based on the results of the study indicate that the problem based learning model of learning is more effectively used than the discovery learning model.